The Sky for a Ceiling - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses how to design a terrace for one's home. Provides suggestions for furniture, color schemes, and maintenance of outdoor furniture. Includes instructions for painting outdoor furniture and describes a terrace for inspiration. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Terrace houses; Paint materials; Outdoor living spaces; Outdoor living spaces--Decoration; Varnish and varnishing; Outdoor furniture; Paint industry and trade; Advertising--Paint